Preparation of a New Acrylonitrile Co-Polymer and Studying the Flammability and Mechanical Properties of Its Composites - Mohammad N AL-Baiati (Journal of Global Pharma Technology, 2017)
Acrylonitrile co-polymer was prepared, by four steps, the first was prepared the hetro-cyclic monomer,the second include prepared linear polymer, the third step includes prepared partially cross-linkedpolymer and the fourth step includes added four different moles (0.5, 1.0, 1.5 and 2.0 mole) ofacrylonitrile monomer. The effect of four types of inorganic phosphors salts in four different weightpercentage (0.2, 0.4, 0.6 and 0.8%), on flammability and mechanical properties (Flexural and Tensile)strength of co- polymer, has been studied. Four standard test methods used to measure the flameretardation and mechanical properties, which are: ASTM: D–2863, ASTM: D–635,ASTM: D – 790 andASTM:D-638.Results obtained from these tests indicated that, the co-polymer which prepared has highvalue of flame retardant and mechanical properties comparing with any thermosetting polymer, on theother hand, additive IV has high efficiency as a flame retardant and high effect on the values ofmechanical properties, but additive I show low effect on retard composition and low effect on the valuesof mechanical properties. This ability to flame retardency increased with the increasing in the number ofmonomers of acrylonitrile.Keywords: Polymer, Modified co-polymer, Acrylonitrile co-polymer, Condensation Polymerization, Fireretardant, Flammability, Additives.